Nation, State and Territorial Unity : a Trans-Outaouais View - Burghardt, Andrew (Cahiers de géographie du Québec, 1980)
The concept of "nation" is currently being applied on more than one level. Whereas many Québécois maintain that a nation should be a state, world experience shows many nations as forming constituent parts of larger-scaled nations. Sovereignty must be seen as having priority over "association". A secession of Québec would split Canada into at least three portions, and would cause a reorientation of the remnant pieces away from the centre. Several potential boundary problems would exist. The recent development of a Canadian nationalism should not be overlooked.